Utility and usability of a dengue NS1 rapid diagnostic as a self-test - Nurfatihah Zulkifli; Naim Che-Kamaruddin; Atiqah Hazan; Tan Kim-Kee; Sivalingam Rajagopal; Sazaly AbuBakar (Tropical Medicine and Health)
Abstract Background Early detection of dengue fever is pivotal to help differentiate against other febrile illnesses, especially in the dengue-endemic regions. Currently, febrile patients would have to go to the healthcare facility to get tested for dengue. A diagnostic approach that empowers febrile persons to perform their own tests is needed. Here, we evaluated the utility and the usability of the dengue NS1 rapid diagnostic test and whether it could be accepted as a home self-test. A lateral flow immunochromatography test (ICT) using DENV NS1 was converted to a possible self-test kit by providing the kit with a test device, an alcohol swab, a lancet, a disposable dropper, an assay buffer, and a test manual. Methods Twenty volunteers were recruited for this study. The participants performed the self-test under the observation of trained observers who recorded if any procedural error was committed. The results of each test were interpreted by the participants using a given interpretation table. Results Ninety-five percent (95%) of the study participants found the instruction manual was easy to follow and 70% felt the test kit was easy to use. Additionally, 80% of the participants successfully obtained the expected results. A majority (80%) would consider using the test kit if needed and would recommend it to family members and friends. Seventy percent (70%) of the participants, most of whom with monthly income of less than USD417, were willing to pay less than USD2 for the test kit. Conclusion Findings from the study suggested that a self-test diagnostic for dengue fever is highly acceptable and, hence, could be a viable approach for the early detection of the infection. Trial registration MRECID.NO: 2022628-11345.